The type of tutor influences the growth and production characters of black pepper cultivars in northeastern Pará-Brazil (Research, Society and Development, 2022)
The black pepper tree is a vine that needs a tutor for its best performance, and it allowed the use of gliricidia as an alternative use to the hardwood season in traditional cultivation, there are few studies on the behavior of the black pepper tree in that tutor. The objective of this work was to compare cultivars of this species in two types of tutors, gliricidia and wooden stake, to verify characters of growth and production of pepper. The tutors were implanted before planting the black pepper seedlings according to the established cultivation recommendations and the experiment was carried out in GRBD considering the tutors, five cultivars and 20 plants per cultivar. Morphological and production characters were evaluated, which were submitted to analysis of variance, followed by Tukey's test at the 5% level. Some characters were influenced by the type of tutor, being positive the use of the live tutor for plant height, however, Cingapura had greater plant height when cultivated using the traditional system. Uthirankotta, Kuthiravally and Clonada presented greater petiole length in gliricidia cultivation and Bragantina presented greater ear length and weight in the same condition, making it advantageous. Therefore, the type of tutor influences the growth and production characters of the cultivars, and gliricidia cultivation may be advantageous for some cultivars.